Heart failure with preserved ejection fraction; the other half of the heart failure, how it stands in 2013 - Shaha, Kunal Bikram; Tamrakar, Rikesh; KC, Man Bahadur; Sharma, Deewakar; Bhatt, Yadav Deo; Rajbhandari, Sujeeb; Sharma, Rajit; Simkhada, Rabindra (Nepalese Heart Journal, 2014)
Last two decade, heart failure with preserved ejection fraction was deprived from being considered as a part of spectrum of heart failure. May be heart failure with preserved ejection fraction was common but not recognized by cardiology fraternity. Heart failure with reduced ejection fraction and heart failure with preserved ejection fraction each make up about half of the overall heart failure burden. But the paradox is: morbidity and mortality in heart failure with preserved ejection fraction despite being similar to patients with heart failure with reduced ejection fraction, today’s cardiology community has not much to offer in terms of mortality reducing treatment. The term diastolic heart failure has been well replaced by heart failure with preserved ejection fraction because multiple non-diastolic abnormalities in cardiovascular function also contribute to heart failure with preserved ejection fraction and diastolic dysfunction always accompanied heart failure with reduced ejection fraction. Diagnosis of heart failure with preserved ejection fraction is an uphill task since it relies upon careful clinical evaluation, doppler (pulse wave and tissue) echocardiography, and invasive hemodynamic assessment after exclusion of potential noncardiac causes of symptoms suggestive of heart failure. Patients with heart failure with preserved ejection fraction are usually older women with a history of hypertension. Obesity, coronary artery disease, diabetes mellitus, and atrial fibrillation are also highly prevalent in heart failure with preserved ejection fraction. Cornerstone of treatment of this entity revolves around treatment of underlying cause and symptom guided therapy. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 46-56 DOI: http://dx.doi.org/10.3126/njh.v10i1.9747